Peran Fear of Negative Evaluation Terhadap Body Dissatisfaction pada Perempuan Emerging Adulthood - Lubis, Raihani Akmalia; Yasmin, Maya (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The aim of this study is to determine the role of fear of negative evaluation on body dissatisfaction in emerging adulthood women. Cluster sampling was used as a sampling technique with a total of 411 women aged 18 to 25 years in West Sumatra. The measurement instrument for fear of negative evaluation and body dissatisfaction used in this study is a questionnaire. The data from the questionnaire results were analyzed using a simple regression test. The results of a simple regression analysis showed a significance value of 0.000 (p < 0.05) which means that fear of negative evaluation plays a role in body dissatisfaction in the group of women in the emerging adulthood stage with a determination coefficient (R square) value of 0.230. This value means that fear of negative evaluation plays a role in 23% of body dissatisfaction in emerging adulthood women, while the remaining 77% is influenced by other factors